Mapping the placental galectin-3 interactome identifies CD9 and ITGB1 as functional glycoprotein counterreceptors during syncytialization - Abigail E. Reeves; Gil-Suk Yang; Sabyasachi Baboo; Jolene K. Diedrich; Pranali Bedekar; Shaheen A. Farhadi; Arun Wanchoo; Christopher Bratcher; Gregory A. Hudalla; John R. Yates; Mia L. Huang (Proceedings of the National Academy of Sciences, 2025)
The fetomaternal interface is replete with glycan-binding proteins (GBPs) that can interact with cell surface glycoprotein counterreceptors to regulate placental function. Here, we interrogate the role of galectin-3, a GBP that controls placental trophoblast syncytialization, an important differentiation process where progenitor cytotrophoblast cells fuse to produce the multinucleated syncytiotrophoblast. The molecular mechanism of galectin-3-mediated fusion has not yet been elucidated in part due to the difficulty of studying glycan-GBP binding events in live cells. To overcome these challenges, we employ a proximity labeling strategy to identify the galectin-3 interactome. From this interactome dataset, we selected and validated CD9 and integrin beta 1 as functional counterreceptors of galectin-3 and showed that CD9 is glycosylated with an N-linked glycan at a rare noncanonical sequon. Furthermore, we present evidence that galectin-3 acts to physically alter the fluidity of the cellular membrane, and it does not activate canonical syncytialization signaling pathways. Overall, we report that galectin-mediated binding events and their corresponding functions in cell biology can be precisely regulated by select glycoproteins at specific glycosites.